Correlation of Coagulation Parameters With Clinical Outcomes During the Coronavirus-19 Surge in New York: Observational Cohort - Reyes Gil, Morayma; Gonzalez-Lugo, Jesus D.; Rahman, Shafia; Barouqa, Mohammad; Szymanski, James; Ikemura, Kenji; Lo, Yungtai; Billett, Henny H. (Frontiers in Physiology, 2021)
Importance: COVID-19 has caused a worldwide illness and New York became the epicenter of COVID-19 in the United States from Mid-March to May 2020. Objective: To investigate the coagulopathic presentation of COVID and its natural course during the early stages of the COVID-19 surge in New York. To investigate whether hematologic and coagulation parameters can be used to assess illness severity and death. Design: Retrospective case study of positive COVID inpatients between 3/20/2020-3/31/2020. Setting: Montefiore Health System main hospital, Moses, a large tertiary care center in the Bronx. Participants: Adult inpatients with positive COVID tests hospitalized at MHS. Exposure (for observational studies): Datasets of participants were queried for demographic (age, sex, socioeconomic status and self-reported race and/or ethnicity), clinical and laboratory data. Main Outcome and Measures: Relationship and predictive value of measured parameters to mortality and illness severity. Results: Of the 225 in this case review, 75 died during hospitalization while 150 were discharged home. Only the admission PT, absolute neutrophil count (ANC) and first D-Dimer could significantly differentiate those who were discharged alive and those who died. Logistic regression analysis shows increased odds ratio for mortality by first D-Dimer within 48 hrs. of admission. The optimal cut-point for the initial D-Dimer to predict mortality was found to be 2.1 g/mL. 15% of discharged patients required readmission and more than a third of readmitted patients died (5% of all initially discharged). Conclusions: We describe here a comprehensive assessment of hematologic and coagulation parameters in COVID-19 and examine the relationship of these to mortality. We demonstrate that both initial and maximum D-Dimer values are biomarkers that can be used for survival assessments. Furthermore, D-Dimer may be useful to follow up discharged patients.